Predictors and moderators of improved social‐emotional functioning in mothers with substance use disorders and their young children enrolled in a relationship‐based case management program. Issue 5 (23rd June 2020) - Hildebrandt, Ursula C.; Graham, J. Christopher; Grant, Therese M.
ABSTRACT: Mothers with substance use disorders (SUDs) typically have trauma histories and psychosocial difficulties that lead to poor social‐emotional functioning and disrupted mother–child relationships. This 12‐month study explored associations of family adverse circumstances and services (case management, therapeutic, and community‐based) received by 57‐mothers with SUDs and their infants (less than 24‐months‐old) with changes in social‐emotional functioning. All mothers were enrolled in a relationship‐based case management program (Parent–Child Assistance Program [PCAP]) that emphasized connecting mothers to appropriate community services. A subset of mothers was additionally provided a trauma‐focused psychotherapeutic intervention (infant–parent psychotherapy [IPP]). Dyads in both treatment groups improved in overall social‐emotional functioning as assessed by the Functional Emotional Assessment Scale (FEAS). A combined‐sample regression analysis revealed that improved FEAS scores were significantly predicted by the number of community services received but not by PCAP case management hours (IPP was not included in this analysis). More adverse circumstances were associated with less improvement in social‐emotional functioning in the children; but among the mothers trauma level did not predict FEAS scores. We also found a moderating effect of trauma: Dyads with relatively more adversity showed a significantly greater association of community services received with improvement in FEAS scores than did those with relatively less adversity. RESUMEN: Las madres con trastornos por abuso de sustancias (SUDs) típicamente tienen historias de trauma y dificultades sicosociales que conducen al débil funcionamiento socio‐emocional y relaciones madre‐niño trastornadas. Este estudio de 12 meses exploró asociaciones entre circunstancias adversas de familia y servicios (de dirección de caso, terapéuticos, basados en la comunidad) que recibieron 57 madres con SUDs y sus infantes (menos de 24 meses de edad) con cambios en el funcionamiento socio‐emocional. Todas las madres fueron inscritas en un programa de dirección de caso con base en la relación (Programa de Asistencia al Progenitor y Niño ‐ PCAP) que enfatizaba la conexión de las madres con adecuados servicios comunitarios. Un subgrupo de madres recibió además una intervención sicoterapéutica con enfoque en el trauma (Sicoterapia de Infante‐Progenitor ‐ IPP). Las díadas en ambos grupos de tratamiento mejoraron en el funcionamiento socio‐emocional en términos generales tal como se les evaluó por medio de la Escala Funcional de Evaluación Emocional (FEAS). Un análisis de regresión que combinó los grupos muestras reveló que los mejorados puntajes en FEAS habían sido pronosticados significativamente por el número de servicios comunitarios recibidos, pero no por las horas del programa de dirección de caso PCAP (no se incluyó la IPP en este análisis). Se asociaron las circunstancias más adversas con un menor mejoramiento en el funcionamiento socio‐emocional en los niños; pero entre las madres, el nivel del trauma no predijo los puntajes FEAS. También encontramos un efecto moderador del trauma: las díadas con más adversidad relativamente mostraron significativamente mayor asociación de servicios comunitarios recibidos con mejoras en los puntajes FEAS que aquellas con menor adversidad relativamente. Palabras claves : Salud mental infantil, trastornos maternos por abuso de sustancias, trauma, servicios comunitarios, Sicoterapia de Infante‐Progenitor RÉSUMÉ: Les mères ayant des troubles liés à la toxicomanie (TLT) ont typiquement des passés de trauma et des difficultés psychosociales qui mènent à un mauvais fonctionnement socio‐émotionnel et à des relations mère‐enfant perturbées. Cette étude de 12 mois a exploré les liens de circonstances familiales adverses et les services (gestion des cas, services thérapeutiques, et services au niveau de la communauté) reçus par 57 mères ayant des TLT et leurs bébés (moins de 24 mois) avec des changements dans le fonctionnement socio‐émotionnel. Toutes les mères ont été inscrites dans un programme de gestion de cas basé sur la relation (Programme d'Assistance Parent‐Enfant) mettant l'accent sur la référence des mères aux services communautaires appropriés. Un sous‐groupe de mères a en plus reçu une intervention psychothérapeutique centrée sur le trauma (Psychothérapie Bébé‐Parent). Les dyades des deux groupes de traitement se sont améliorées dans le fonctionnement socio‐émotionnel général, évalué par l'Echelle d'Evaluation Emotionnelle Fonctionnelle (Functional Emotional Assessment Scale, soir FEAS). Une analyse de régression d'échantillons combinés a révélé que les scores FEAS améliorés étaient fortement prédits par le nombre de services communautaires reçus mais pas par les heures de gestion de cas FCAP (l'IPP n'a pas été inclue dans cette analyse). Plus de circonstances adverses était lié à moins d'amélioration dans le fonctionnement socio‐émotionnel chez les enfants. Mais chez les mères le niveau de trauma ne prédisait pas les scores FEAS. Nous avons aussi découvert un effet modérateur du trauma: les dyades avec relativement plus d'adversité faisaient preuve d'une association bien plus élevée avec les services communautaires reçus avec une amélioration dans les scores FEAS que les dyades avec relativement moins d'adversité. Mots clés : Santé Mentale du Nourrisson, Troubles Liés à la Toxicomanie Maternelle, Trauma, Service Communautaires, Psychothérapie Bébé‐Parent ZUSAMMENFASSUNG: Prädiktoren und Moderatoren einer verbesserten sozial‐emotionalen Funktionsfähigkeit bei Müttern mit Substanzstörungen und ihren kleinen Kindern im Kontext eines beziehungsbasierten Fallmanagementprogramms Bei Müttern mit Substanzstörungen (substance use disorders; SUDs) gibt es oft traumatische Erlebnisse in der Vergangenheit und psychosoziale Schwierigkeiten, die zu einer schlechten sozial‐emotionalen Funktionsfähigkeit und gestörten Mutter‐Kind‐Beziehungen führen können. Diese 12 Monate lange Studie untersuchte Assoziationen zwischen widrigen familiären Umständen und Leistungen (Fallmanagement, therapeutisch Leistungen und gemeindebasierte Leistungen), die 57 Mütter mit SUDs und ihre Säuglinge (unter 24 Monaten) mit veränderter sozial‐emotionaler Funktionsfähigkeit erhalten haben. Alle Mütter nahmen an einem beziehungsbasierten Fallmanagementprogramm (Parent‐Child Assistance Program; PCAP) teil, bei dem der Schwerpunkt auf der Vermittlung der Mütter an geeignete gemeindebasierte Leistungen lag. Ein Teil der Mütter erhielt zusätzlich eine traumafokussierte psychotherapeutische Intervention (Infant‐Parent Psychotherapy; IPP). In beiden Behandlungsgruppen verbesserte sich die sozial‐emotionale Gesamtfunktionsfähigkeit, was anhand der Functional Emotional Assessment Scale (FEAS) festgestellt werden konnte. Eine Regressionsanalyse ergab, dass verbesserte FEAS‐Scores signifikant durch die Anzahl der erhaltenen gemeindebasierten Leistungen, jedoch nicht durch die PCAP‐Fallmanagementstunden vorhergesagt wurden (IPP wurde in dieser Analyse nicht berücksichtigt). Ein größeres Ausmaß an widrigen Umständen war mit einer geringeren Verbesserung der sozial‐emotionalen Funktionsfähigkeit bei den Kindern assoziiert. Bei den Müttern konnten die FEAS‐Werte jedoch nicht von den traumabezogenen Daten vorhergesagt werden. Außerdem wurde einen moderierenden Effekt von Trauma gefunden: Mutter‐Kind Dyaden mit verhältnisweise widrigeren Umständen zeigten eine signifikant größere Assoziation zwischen erhaltenen gemeindebasierten Leistungen und verbesserten FEAS‐Werten, als solche mit weniger widrigen Umständen. Stichwörter : Psychische Gesundheit von Säuglingen, Substanzkonsumstörungen bei Müttern, Trauma, gemeindebasierte Leistungen, Eltern‐Kind Psychotherapie 抄録: 関係性を基盤としたケース・マネージメント・プログラムに参加している物質使 用障害の母親とその乳幼児における社会性と情動の機能の改善に関わる予測因子 と緩和因子 物質使用障害(SUDs)の母親は、一般的に貧弱な社会性と情動の機能と混乱した母 子関係につながるトラウマの過去と心理社会的困難性を抱えている。12か月にわ たる本研究では、57組のSUDsの母親とその乳幼児(生後24か月未満)の社会性と情 動の機能における変化が、家族の逆境と受けたサービス(ケース・マネージメン ト、治療的、地域社会を基盤にした)とどのように関連しているかについて研究 した。すべての母親は、母親たちが適切な地域社会のサービスと繋がることに重 点を置いたケース・マネージメント・プログラム(親子支援プログラムPCAP)に在 籍していた。母親たちの一つの集団は、トラウマに焦点を当てた精神療法的介入 (乳児−親精神療法IPP) を追加で提供されていた。両治療グループの母子は機 能的情動評価尺度(FEAS)の評価において、総体的に社会性と情動の機能に改善が 見られた。複合標本回帰分析は改善したFEAS値が、PCAPのケース・マネージメン トの時間数ではなく、受けている地域社会のサービス数に有意に予測された(IPP は、この分析には含まれなかった)。より深刻な逆境が、子どもにおける社会性 情動機能のより少ない改善と関連していた。しかし、母親においては、トラウマ レベルが、FEAS値を予測することはなかった。我々はまた、トラウマの緩和効果 を発見した。つまり、より深刻な逆境にいる母子は、比較的逆境が少ない母子に 比べて受けた地域社会のサービスとFEAS値の改善とに有意に大きな関連が見られ た。 キーワード: 乳幼児精神保健、母親の物質使用障害、トラウマ、地域社会のサ ービス 摘要: 患有物质使用障碍 (SUDs) 的母亲通常有创伤史和社会心理障碍, 这会导致其不良的社交情感技能并破坏母子关系。这项为期12个月的研究探讨了57名患有SUDs的母亲及其婴儿 (不超过24个月大) 接受到的家庭不利环境和服务 (病例管理、治疗和社区化服务) 与社交情感技能变化之间的关系。所有母亲都参加了一个基于良好关系的病例管理计划 (亲子援助计划, PCAP), 该方案强调将母亲与适当的社区服务联系起来。此外, 还为一部分母亲提供了针对创伤的心理治疗干预措施 (母婴心理治疗, IPP) 。通过功能性情绪评估量表 (FEAS) 评估, 两个治疗组的母婴在整体社交情感技能上均有改善。组合样本回归分析显示, 母婴接受到的社区服务数量能够显著预测FEAS分数的改善, 但PCAP的病例管理时长不能预测 (该分析不包括IPP) 。不利的环境越多, 儿童社交情感技能的改善就越少;但是, 母亲的创伤水平并不能预测FEAS分数。我们还发现了创伤的调节作用:与遭受逆境较少的母婴相比, 遭受逆境较多的母婴, 其接受到的社区服务与FEAS分数改善之间的关联度显著提高。 关键词: 婴儿心理健康, 母体物质使用障碍, 创伤, 社区服务, 母婴心理治疗 ملخص: عوامل التنبؤ والمتغيرات الوسيطة في تحسين الأداء الاجتماعي والعاطفي عند الأمهات المصابات باضطرابات تعاطي المخدرات وأطفالهن الصغار المسجلين في برنامج لإدارة الحالات قائم على العلاقات ملخص عادة ما تعاني الأمهات المصابات باضطرابات تعاطي المخدرات من صدمات وصعوبات نفسية اجتماعية تؤدي إلى ضعف الأداء الاجتماعي والعاطفي وإلى اضطراب العلاقات بين الأم والطفل. استكشفت هذه الدراسة التي استمرت 12 شهرًا الارتباطات بين الظروف الأسرية الصعبة والخدمات (إدارة الحالات والخدمات المجتمعية والعلاجية) التي تلقتها 57 من الأمهات (ذوي اضطرابات تعاطي المخدرات) وأطفالهن الرضع (أقل من 24 شهرًا) الذين يواجهون تغيرات في الأداء الاجتماعي العاطفي. والتحقت جميع الأمهات ببرنامج لإدارة الحالات قائم على العلاقات (برنامج مساعدة الوالدين والأطفال) الذي شدد على ربط الأمهات بالخدمات المجتمعية المناسبة. بالإضافة إلى ذلك، تم توفير مجموعة فرعية من الأمهات لتدخلات نفسية تركز على الصدمات النفسية (العلاج النفسي للرضع والوالدين). تحسنت الثنائيات في كلتا المجموعتين من حيث الأداء الاجتماعي العاطفي العام كما تم تقييمها من قبل مقياس التقييم العاطفي الوظيفي (FEAS). وكشف تحليل الانحدار المشترك أن تحسن درجات الـ FEAS قد تنبأ به إلى حد كبير عدد الخدمات المجتمعية الواردة وليس ساعات إدارة الحالات في البرنامج (لم يدرج IPP في هذا التحليل). وترتبط الظروف الأكثر سلبية بتحسن أقل في الأداء الاجتماعي ‐ العاطفي لدى الأطفال؛ ولكن بين الأمهات، لم يتنبأ مستوى الصدمة بدرجات FEAS. كما وجدنا تأثيرًا معتدلًا للصدمة: أظهرت الثنائيات ذات الشدائد الأكثر نسبيًا ارتباطًا أكبر بكثير من الخدمات المجتمعية التي تم تلقيها مع تحسن في درجات FEAS من تلك التي لديها صعوبات أقل نسبيًا. الكلمات الرئيسية: الصحة النفسية للرضع، اضطرابات تعاطي المخدرات الأمومية، الصدمات النفسية، الخدمات المجتمعية، العلاج النفسي للرضع والوالدين